Psychosocial therapy and causes of death after deliberate self-harm: a register-based, nationwide multicentre study using propensity score matching. Issue 16 (22nd September 2016) - Birkbak, J.; Stuart, E. A.; Lind, B. D.; Qin, P.; Stenager, E.; Larsen, K. J.; Wang, A. G.; Nielsen, A. C.; Pedersen, C. M.; Winsløv, J.-H.; Langhoff, C.; Mühlmann, C.; et al.
Abstract : Background: Psychosocial therapy after deliberate self-harm might be associated with reduced risk of specific causes of death. Method: In this matched cohort study, we included patients, who after an episode of deliberate self-harm received psychosocial therapy at a Suicide Prevention Clinic in Denmark between 1992 and 2010. We used propensity score matching in a 1:3 ratio to select a comparison group from 59 046 individuals who received standard care. National Danish registers supplied data on specific causes of death over a 20-year follow-up period. Results: At the end of follow-up, 391 (6.9%) of 5678 patients in the psychosocial therapy group had died, compared with 1736 (10.2%) of 17 034 patients in the matched comparison group. Lower odds ratios of dying by mental or behavioural disorders [0.54, 95% confidence interval (CI) 0.37–0.79], alcohol-related causes (0.63, 95% CI 0.50–0.80) and other diseases and medical conditions (0.61, 95% CI 0.49–0.77) were noted in the psychosocial therapy group. Also, we found a reduced risk of dying by suicide as well as other external causes, however, not by neoplasms and circulatory system diseases. Numbers needed to treat were 212.9 (95% CI 139.5–448.4) for mental or behavioural disorders as a cause of death, 111.1 (95% CI 79.2–210.5) for alcohol-related causes and 96.8 (95% CI 69.1–161.8) for other diseases and medical conditions. Conclusions: Our findings indicate that psychosocial therapy after deliberate self-harm might reduce long-term risk of death from select medical conditions and external causes. These promising results should be tested in a randomized design.